Explanation:
Simplifying
8x + -2(3x + -4 + 2y) + -12x = 0
Reorder the terms:
8x + -2(-4 + 3x + 2y) + -12x = 0
8x + (-4 * -2 + 3x * -2 + 2y * -2) + -12x = 0
8x + (8 + -6x + -4y) + -12x = 0
Reorder the terms:
8 + 8x + -6x + -12x + -4y = 0
Combine like terms: 8x + -6x = 2x
8 + 2x + -12x + -4y = 0
Combine like terms: 2x + -12x = -10x
8 + -10x + -4y = 0
Solving
8 + -10x + -4y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-8' to each side of the equation.
8 + -10x + -8 + -4y = 0 + -8
Reorder the terms:
8 + -8 + -10x + -4y = 0 + -8
Combine like terms: 8 + -8 = 0
0 + -10x + -4y = 0 + -8
-10x + -4y = 0 + -8
Combine like terms: 0 + -8 = -8
-10x + -4y = -8
Add '4y' to each side of the equation.
-10x + -4y + 4y = -8 + 4y
Combine like terms: -4y + 4y = 0
-10x + 0 = -8 + 4y
-10x = -8 + 4y
Divide each side by '-10'.
x = 0.8 + -0.4y
Simplifying
x = 0.8 + -0.4y